Excito-Repellency Effects of Salvia sclarea L. (Lamiaceae) Extracts on Adult House Flies, Musca domestica L. (Diptera: Muscidae) - Mohammad Reza Fakoorziba; Mohammad Djaefar Moemenbellah-Fard; Kourosh Azizi; Heshmatollah Shekarpoor; Hamzeh Alipoor (Shiraz University of Medical Sciences, 2014)
Background: Medicinal plant extracts such as those obtained from Salvia species have a wide variety of chemical compounds in their essential oils. The repellency of a number of essential oils including those from the labiates like Salvia against several insect species including the common house flies is reported. Objective: The aim of this investigation was to find out the excito-repellency effects of Salvia sclarea L. (Lamiaceae) extracts against adult house flies, Musca domestica L. (Diptera: Muscidae). Methods: Air-dried plant material from the aerial parts of S. sclarea was subjected to hydro-distillation in a Clevenger type glass apparatus model Soxhlet with acetone, benzene, petroleum ether, chloroform, and aqueous solvents. Only adult house flies were inserted into an exposure chamber and their behavior was monitored for feeding tendency, repellency rate and deterrence rate. Statistical analyses were carried out by one-way analysis of variance (ANOVA) with computation of the significance of differences in the outcome of various treatments. Results: There were significant differences among most of the various extracts with their controls in the sequential effects of feeding (P=0.04), deterrent (P=0.023) and repellency (P=0.01) rates of house flies. The order of potency for various extracts with a concentration of 100 g/l was as follows: petroleum ether> benzene> water> acetone> chloroform. Conclusion: It is thus conceivable to search for native means of combating house flies by fractionating the active ingredients in the Clary sage in the light of its excito-repellency effects.